Examining the Pueblo II–III Transition in the Moapa Valley, Southern Nevada. Issue 4 (2nd October 2019) - Harry, Karen G.; Perez, Daniel M.
Abstract : Based on the limited data available to her at the time, Margaret Lyneis proposed that the transition between the Pueblo II and Pueblo III periods in the Moapa Valley was marked by differences in social organization and subsistence strategies. Since then, additional data have become available from new archival research and excavations, making it possible to more fully investigate the ideas presented by Lyneis. In this paper, the newly-available data are used to re-evaluate the nature of the Pueblo II–III transition, and their implications for understanding the terminal Virgin Branch occupation of the Moapa Valley are considered.